2016
DOI: 10.1002/2015jc010904
|View full text |Cite
|
Sign up to set email alerts
|

Mesoscale resolution capability of altimetry: Present and future

Abstract: Wavenumber spectra of along‐track Sea Surface Height from the most recent satellite radar altimetry missions [Jason‐2, Cryosat‐2, and SARAL/Altika) are used to determine the size of ocean dynamical features observable with the present altimetry constellation. A global analysis of the along‐track 1‐D mesoscale resolution capability of the present‐day altimeter missions is proposed, based on a joint analysis of the spectral slopes in the mesoscale band and the error levels observed for horizontal wavelengths low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

32
224
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 165 publications
(257 citation statements)
references
References 42 publications
32
224
1
Order By: Relevance
“…It clearly stresses the better match between the true SSH fields and the reconstruction using model (2) compared to the optimally-interpolated field. As such, model (2) provides a more consistent view of the spectral properties of the upper ocean dynamics [3]. FIGURE 2: High-resolution SSH reconstruction, February, 10, 2010 : first row, from left to right, high-resolution SSH, lowresolution SSH, reconstructed SSH using model (2) with parameterization H 1,Iso + H 2,Iso , high-resolution SST detail ; second row, from left to right, gradient magnitudes of the high-resolution, low-resolution , and reconstructed SSH fields of the highresolution SSH (magenta), low-resolution SSH (black), reconstructed SSH (blue) and high-resolution SST (cyan).…”
Section: B Resultsmentioning
confidence: 99%
“…It clearly stresses the better match between the true SSH fields and the reconstruction using model (2) compared to the optimally-interpolated field. As such, model (2) provides a more consistent view of the spectral properties of the upper ocean dynamics [3]. FIGURE 2: High-resolution SSH reconstruction, February, 10, 2010 : first row, from left to right, high-resolution SSH, lowresolution SSH, reconstructed SSH using model (2) with parameterization H 1,Iso + H 2,Iso , high-resolution SST detail ; second row, from left to right, gradient magnitudes of the high-resolution, low-resolution , and reconstructed SSH fields of the highresolution SSH (magenta), low-resolution SSH (black), reconstructed SSH (blue) and high-resolution SST (cyan).…”
Section: B Resultsmentioning
confidence: 99%
“…By calculating wavenumber spectra from along-track SSH anomalies from the recent missions, we have been able to estimate the background noise levels of each mission, and the corresponding observable ocean scales, where the signal-to-noise is greater than 1. This statistical estimate of the altimetric noise and the observable scales has been performed over the global oceans using Jason-2 (Ku-band), SARAL/AltiKa (Ka-band) and CryoSat-2 in low-resolution mode (LRM) by [5], and from Jason-2, SARAL/AltiKa and Sentinel-3 in Synthetic Aperture Radar (SAR) mode by [6]. Regional analyses have also been performed over the western Mediterranean Sea by [7] using Jason-2, SARAL/AltiKa and CryoSat-2 SAR mode.…”
Section: Observability Of the Fine-scale Ocean Dynamicsmentioning
confidence: 99%
“…During the last few years there have been major improvements in radar altimetry technology that have not only reduced noise levels (Dufau et al, 2016) but also reduced the impact of inhomogeneities in measurements (Dibarboure et al, 2014). Nevertheless, current altimeters still present strong limitations in observing small-scale features O(10 km) not only due to noise but also due to temporal sampling (Chavanne and Klein, 2010).…”
Section: Currents From Sea Surface Heightmentioning
confidence: 99%
“…Moreover, the level of noise strongly depends on the sea state, which makes it highly variable in space and time, implying that the effective resolution of altimetric measurements is also variable. In a recent study, Dufau et al (2016) have shown that the smallest scale that can be resolved by the new generation of altimeters is 40-50 km in areas of strong currents, but it can be as large as 90-100 km. This variability has motivated the development of adaptive approaches to better exploit the sampling capabilities of current altimeters (Isern-Fontanet et al, 2016a).…”
Section: Currents From Sea Surface Heightmentioning
confidence: 99%